2014
DOI: 10.1590/1678-476620141043269276
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do fotoperíodo sobre o ciclo de vida e a morfometria da concha de Dysopeas muibum (Mollusca, Subulinidae) em condições de laboratório

Abstract: ABSTRACT. Effect of photoperiod on the life cycle and shell morphology of Dysopeas muibum (Mollusca, Subulinidae) under laboratory conditions This study aimed to evaluate the effect of photoperiod on the life cycle and shell morphology of Dysopeas muibum Marcus & Marcus, 1968 under laboratory conditions. To this end, we conducted monitoring growth of the shell, the release of puppies and mortality of 40 specimens undergo natural conditions of temperature, relative humidity and photoperiod, and 80 undergo contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Studies with other arthropods, including crabs, Pseudocarcinus gigas Lamarck (Decapoda: Menippidae) (Gardner & Maguire, 1998), hemipterans, Orius niger Wolff (Hemiptera: Anthocoridae) (Bahşi & Tunç, 2008), and mollusks, Dysopeas muibum Marcus and Marcus (Mollusca: Subulinidae) (Pilate et al, 2014), suggested that the photoperiod does not affect the survival of these organisms but could affect other biological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with other arthropods, including crabs, Pseudocarcinus gigas Lamarck (Decapoda: Menippidae) (Gardner & Maguire, 1998), hemipterans, Orius niger Wolff (Hemiptera: Anthocoridae) (Bahşi & Tunç, 2008), and mollusks, Dysopeas muibum Marcus and Marcus (Mollusca: Subulinidae) (Pilate et al, 2014), suggested that the photoperiod does not affect the survival of these organisms but could affect other biological parameters.…”
Section: Discussionmentioning
confidence: 99%